Association between Comorbidities and COVID-19 Mortality: a Cross-Sectional Study in a Community Health Center in Indonesia - Sutaip, Sutaip; Sutiningsih, Dwi; Adi, Mateus Sakundarno; Diyana, Sutra; Rahayu, Siti; Azizah Azzahra, Nur; Andalusia Sarigando Banilai, Puti; Giyantolin, Giyantolin (International Journal of Integrated Health Sciences, 2023)
Objective: To analyze the risk factors for mortality and comorbidity of COVID-19 patients in a public health center work area in Indonesia.Methods: This was a cross-sectional observational analytic quantitative study using secondary data of 820 confirmed COVID-19 cases in Brebes Public Health Center work area during the period of June 2020–December 2021. Univariate and bivariate analyses were used to analyze the obtained data statistically with a p-value of <0.005 considered significant.Results: Of the 820 confirmed COVID-19 patients, 85.1% recovered and 15.0% died. Analysis on the characteristics of these cases showed that 51.2% females and 48.8 %  males were included in this study, with 77.6% of them were <60 years old. No history of comorbidities was identified in 92.1% of the cases. In remaining cases with comorbidities, Diabetes Mellitus was recognized as the most prevalent (n=39, 4.8%).  Results of the Chi-Square test demonstrated that comorbidity status (p-value = 0.001), place of quarantine (p p=0.000 p>0.05), and diabetes (p=0.000, OR=2.87,  95% CI 19 1.24-0280) were significantly associated with mortality.Conclusion: Comorbidity status, diabetes, and the place quarantine are risk factors for mortality among COVID-19 confirmed cases, especially in Brebes Public Health Center work area. Thus, it is important to increase knowledge about COVID-19 prevention and risks to prevent transmission among those with higher risks for mortality. Further studies on factors related to sustainable supports for COVID-19 patients are also necessary.